Incorporating eyebrow and eye state information for facial expression recognition in mask-obscured scenes - Kun Zheng; Li Tian; Zichong Li; Hui Li; Junjie Zhang (Electronic Research Archive, 2024)
Facial expression recognition plays a crucial role in human-computer intelligent interaction. Due to the problem of missing facial information caused by face masks, the average accuracy of facial expression recognition algorithms in mask-obscured scenes is relatively low. At present, most deep learning-based facial expression recognition methods primarily focus on global facial features, thus they are less suitable for scenarios where facial expressions are obscured by masks. Therefore, this paper proposes a facial expression recognition method, TransformerKNN (TKNN), which integrates eyebrow and eye state information in mask-obscured scenes. The proposed method utilizes facial feature points in the eyebrow and eye regions to calculate various relative distances and angles, capturing the state information of eyebrows and eyes. Subsequently, the original face images with masks are used to train a Swin-transformer model, and the eyebrow and eye state information is used to train a k-Nearest Neighbor (KNN) model. These models are then fused at the decision layer to achieve automated emotion computation in situations when facial expressions are obscured by masks. The TKNN method offers a novel approach by leveraging both local and global facial features, thereby enhancing the performance of facial expression recognition in mask-obscured scenes. Experimental results demonstrate that the average accuracy of the TKNN method is 85.8% and 70.3%, respectively. This provides better support for facial expression recognition in scenarios when facial information is partially obscured.